Navigating the COVID-19 pandemic: Learning experiences of an online Sino-Nordic doctoral summer school on aging - Xu, Wenqian ; 0000-0003-4274-5468; Aavikko, Lotta; Kärnä, Eija; Chen, Honglin; Arief, Muzawir; Motel-Klingebiel, Andreas; An, Ning (Educational Gerontology, 2024)
The COVID-19 pandemic has accelerated the digital transformation of Higher Education, necessitating a rapid shift from in-person to remote teaching and learning. This study investigates the experiences of doctoral students in an online Sino-Nordic summer school on aging, implemented during the pandemic. A survey was conducted to collect and analyze data on participants’ experiences and perspectives. Findings reveal three thematic areas: doctoral students’ learning needs and preferences, contextual factors affecting their learning experiences, and their adaptations to online summer school. Student participants gained diverse insights and expanded their networks, but also faced challenges such as limited social interaction and scheduling conflicts. While some students embraced the online format, most preferred in-person participation as a supplementary or alternative approach in future summer schools. Recommendations for future improvements are creating an empowering learning environment, improving strategic planning and communication among organizing institutions, involving students and stakeholders in training design and implementation, maximizing the use of online features and tools, and optimizing time management.